Meckel-Gruber syndrome: a case report with review of literature - Prasad, Usha; Prasad, Uma; J, Sushma; Lakshmi, A. Bhagya (International Journal of Research in Medical Sciences, 2017)
Meckel Gruber syndrome is an autosomal recessive disorder, characterized by a combination of renal cysts or cystic renal dysplasia, developmental anomalies of the central nervous system, hepatic dysgenesis and polydactyly. It is a rare syndrome with highest incidence in Gujarati Indians and Finnish population. We report a case of Meckel Gruber syndrome in non Gujarati Indian which was diagnosed on fetal autopsy.